Rethink of Individual Transferable Quota Fishery Management System in China: A Case Study in Zhejiang Province, China - Yuan Jiang; Zoe Qu; Huijuan Hao; Siying Wang (International Journal of the Commons)
In light of the successful experience of ITQ-management in many countries’ fishery reforms, the Chinese government has also carried out corresponding reform pilot projects in some cities. But unfortunately, these reforms were not successful. Based on the author’s own participation in the pilot reform of the fishery industry in Zhoushan City, Zhejiang Province, this article analyzes the reasons for the failure of the reform through research methods such as interviews and investigations. This study finds out that on the surface, the reason for the failure is the inaction of local governments, which has led to inadequate definition, transfer, supervision, and protection of fishing rights. However, the underlying reason is the inadequacy of the existing legal system of China’s fishing industry, leading to a lack of corresponding responsibility of local governments, followed by the absence of motivation to reform. This article reveals the close connection between the willingness of local governments in implementing ITQ management and the existing legal design, and explores a neglected key issue— the responsibility of local governments that comply with the ITQ-management method. Although ITQ-management has achieved remarkable results in some developed countries, its failure in China reveals the importance of local government responsibility. Therefore, this article, targeted at the responsibilities of local governments, proposes suggestions like adding ITQ management legal responsibilities to fisheries law, and refining its structure, content and evaluation methods. This research can not only be used for reference by the Chinese legal system, but also by many other countries with inadequate local government responsibilities.